30-hydroxygambogic acid increases the efficacy of cisplatin in an HPV+ head and neck cancer in vivo model - Sonia N. Whang; Valeria Rodarte; Trevor Lohman; Josh Barforough; Lennox Chitsike; Gina N. Lucas; David Lee; Caleb Ruiz-Jimenez; Yan Chen Wongworawat; Rouba Ali-Fehmi; Marya Wahidi; Juli Unternaehrer; et al. (BMC Cancer)
Abstract Background Head and neck squamous cell carcinoma (HNSCC) affects more than half a million people annually, and nearly 80% of oropharyngeal cancer cases are caused by human papillomavirus (HPV). Current treatments include chemo- and radiotherapy, though the effectiveness of these therapies is limited by the viral oncoprotein E6, which disrupts apoptotic pathways by binding and accelerating the degradation of molecules such as E6AP and caspase-8. Our lab has identified an E6 inhibitor, 30-hydroxygambogic acid (GA-OH), that is able to maintain these apoptotic signaling molecules. Method To further explore the therapeutic potential of this small molecule, we determined its antitumor efficacy in vivo. We developed an optimized xenograft model for HPV+ HNSCC, assessed GA-OH’s toxicity, and evaluated the effectiveness of GA-OH in combination with chemotherapy utilizing the optimized concentration of 0.6 mg/kg. Results GA-OH significantly increases (* p = 0.0105) cisplatin’s efficacy in HPV+ HNSCC in vivo without overt clinical manifestations. The only toxicities noted were a 4-fold increase in creatine kinase (**** p < 0.0001) and a 2.4-fold increase in aspartate aminotransferase (** p = 0.0057) in the cisplatin and GA-OH combination group compared to the vehicle group. Conclusion The small molecule GA-OH was tolerable in our murine model, significantly amplifying the efficacy of cisplatin treatment.